DESAIN MODEL KONVERTER DC-DC PENGUATAN TINGGI - Mohammad Adnan; Zainal Abidin; Daniel Kambuno (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research aims to obtain a high gain DC-DC converter system/model design that can be applied to a 400 V DC microgrid system. The high gain DC converter model used is an interleaved boost converter. Parameters used: The voltage at the load is regulated and stable at 400 V, the nominal input voltage is 48 V with a minimum variation of 36 V, the maximum is 60 V, the current at the nominal load is 3 A with a maximum variation of 0 A, 3.5 A. The stages of the research method used are literature review, determining model specifications, creating a model and simulation using Simulink Matlab. The simulation results obtained varied output voltages of 314.1, 400.2, and 511.3.